Pelaksanaan Penilaian Perkembangan Sosial Emosional Anak Usia Dini Di RA Siti Khodijah Karangrowo Wonosalam Demak - Aulina Fitriya (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Developmental assessment is a process of collecting data and then analyzing it to determine the implementation of the assessment of the child's development that is experienced. A child's behavior in adjusting the norms that apply in their environment can be called social development. Emotional development is a condition in the form of feelings that are carried out through actions and create attitudes towards behavior. Social emotional development of early childhood is an ability in children where children can manage and express emotions accordingly. Children can explore with their environment, namely in interacting with their peers. This study aims to find out that teachers will play a role in the implementation of social emotional development assessments and efforts to foster social emotional development in children. In this study using qualitative methods. The results of the study show that the social emotional development of children is different. Research shows that assessments are carried out to see whether the socio-emotional development aspects of children have been achieved or not. This assessment process is an inseparable part of the learning process and is comprehensive (holistic) which includes all aspects of student development, both aspects of attitude, knowledge and skills. The implementation of the assessment of the development of RA Siti Khodijah Karangrowo Wonosalam Demak uses various assessment methods and techniques such as; assessment techniques of observation, conversation, anecdotal notes and specimen records, so that they have the skills to choose and use appropriately the methods and techniques that are considered most appropriate to the objectives and learning process, as well as the learning experience that has been determined.